Lack of Cystic Fibrosis Transmembrane Conductance Regulator in CD3(+) Lymphocytes Leads to Aberrant Cytokine Secretion and Hyperinflammatory Adaptive Immune Responses - Mueller, Christian (American Thoracic Society, 2011)
Cystic fibrosis (CF), the most common fatal monogenic disease in the United States, results from mutations in CF transmembrane conductance regulator (CFTR), a chloride channel. The mechanisms by which CFTR mutations cause lung disease in CF are not fully defined but may include altered ion and water transport across the airway epithelium and aberrant inflammatory and immune responses to pathogens within the airways. We have shown that Cftr(−/−) mice mount an exaggerated IgE response toward Aspergillus fumigatus, with higher levels of IL-13 and IL-4, mimicking both the T helper cell type 2–biased immune responses seen in patients with CF. Herein, we demonstrate that these aberrations are primarily due to Cftr deficiency in lymphocytes rather than in the epithelium. Adoptive transfer experiments with CF splenocytes confer a higher IgE response to Aspergillus fumigatus compared with hosts receiving wild-type splenocytes. The predilection of Cftr-deficient lymphocytes to mount T helper cell type 2 responses with high IL-13 and IL-4 was confirmed by in vitro antigen recall experiments. Conclusive data on this phenomenon were obtained with conditional Cftr knockout mice, where mice lacking Cftr in T cell lineages developed higher IgE than their wild-type control littermates. Further analysis of Cftr-deficient lymphocytes revealed an enhanced intracellular Ca(2+) flux in response to T cell receptor activation. This was accompanied by an increase in nuclear localization of the calcium-sensitive transcription factor, nuclear factor of activated T cell, which could drive the IL-13 response. In summary, our data identified that CFTR dysfunction in T cells can lead directly to aberrant immune responses. These findings implicate the lymphocyte population as a potentially important target for CF therapeutics.